2015
DOI: 10.1016/j.cub.2014.12.009
|View full text |Cite|
|
Sign up to set email alerts
|

Cell-Size Control and Homeostasis in Bacteria

Abstract: SUMMARY How cells control their size and maintain size homeostasis is a fundamental open question. Cell-size homeostasis has been discussed in the context of two major paradigms: sizer, in which the cell actively monitors its size and triggers the cell cycle once it reaches a critical size, and timer, in which the cell attempts to grow for a specific amount of time before division. These paradigms, in conjunction with the “growth law” [1] and the quantitative bacterial cell cycle model [2], inspired numerous t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

92
1,111
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 683 publications
(1,208 citation statements)
references
References 36 publications
(43 reference statements)
92
1,111
5
Order By: Relevance
“…An important distinction between the current study and previous analyses is the measurement of cell size. In our datasets, cell size was measured via a fluorescent protein-based proxy for cell mass, whereas recent work in bacteria and budding yeast has focused on cell volume [6,[11][12][13]. Elements of cell volume in budding yeast, particularly the vacuoles, are known to undergo dynamic, regulated changes over the course of the cell cycle [39].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An important distinction between the current study and previous analyses is the measurement of cell size. In our datasets, cell size was measured via a fluorescent protein-based proxy for cell mass, whereas recent work in bacteria and budding yeast has focused on cell volume [6,[11][12][13]. Elements of cell volume in budding yeast, particularly the vacuoles, are known to undergo dynamic, regulated changes over the course of the cell cycle [39].…”
Section: Resultsmentioning
confidence: 99%
“…Assuming a consistent single-cell growth rate across cells, these tenets are sufficient to maintain a consistent size distribution in the population. Recent studies in bacteria have revealed an alternative size control model by which cells add a relatively constant amount of volume over the cell cycle, regardless of their birth size [11][12][13]. Here we use time-lapse microscopy datasets tracking characteristics of individual cells to test these models and further characterize coordination between growth and division in budding yeast.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the amount of variation in wild type Msm cells (19%) is much higher than Δ lamA Msm cells (12%) (Fig. 4e) and other rod-shaped bacteria, 16, 17 including Corynebacterium glutamicum (Extended Data Fig. 8), a close relative of mycobacteria with similar cell wall architecture and polar elongation but that does not encode LamA.…”
Section: Main Textmentioning
confidence: 93%
“…We used a stochastic hybrid systems approach [52] to simulate a population of exponentially growing cells undergoing 'adder' dynamics [50,51], whereby cells add a constant amount of volume (K v ) to their initial volume (v 0 ) each cell cycle, which has found recent support in bacteria [53]. Cells are modelled to then divide by stochastically partitioning their volume, with the first daughter inheriting volume and Bj€ orklund as a non-heritable parabolic relationship between mitochondrial functionality (which we interpret as rDC) and cell volume v…”
Section: Mathematical Model Of Power Demand Scaling and Cell Deathmentioning
confidence: 99%